Feasibility of the lifestyle integrated functional exercise concept in cognitively impaired geriatric rehabilitation patients - Wolf-Belala, Nacera; Schwenk, Michael (Zeitschrift für Gerontologie und Geriatrie, 2019)
Background and objectiveIncreasing numbers of cognitively impaired older persons are admitted for inpatient hospital treatment. Therefore, new approaches are needed to prevent a loss of mobility during hospital stays and improve outcomes of this vulnerable patient group. The lifestyle integrated functional exercise (LiFE) concept uses activities of daily living (ADL) situations as opportunities to improve balance and strength. A pilot study was performed to test the feasibility and acceptability of the LiFE exercises in a geriatric rehabilitation setting.Methods and patientsA sample of 20 moderately cognitively impaired rehabilitation patients (mean age 84.5 years) tested the feasibility and acceptability of the LiFE exercises.ResultsThe testing resulted in floor effects for every tested exercise. Of the exercises two were too difficult for over the half of the participants, namely stepping over objects and walking on heels. In contrast, the sit to stand exercise was feasible for 95% of the patients. The frequency of floor effects for the remaining exercises varied between 20% and 40%.ConclusionIn this group of moderately cognitively impaired rehabilitation patients the exercises were feasible mostly under supervised conditions and frequently included additional physical support. An adjustment of the LiFE exercises in this setting is required before a trial should be performed in the acute care setting.